Pulsed Electromagnetic Fields Partially Preserve Bone Mass, Microarchitecture, and Strength by Promoting Bone Formation in Hindlimb‐Suspended Rats. (October 2014) - Jing, Da; Cai, Jing; Wu, Yan; Shen, Guanghao; Li, Feijiang; Xu, Qiaoling; Xie, Kangning; Tang, Chi; Liu, Juan; Guo, Wei; Wu, Xiaoming; Jiang, Maogang; et al.
ABSTRACT A large body of evidence indicates that pulsed electromagnetic fields (PEMF), as a safe and noninvasive method, could promote in vivo and in vitro osteogenesis. Thus far, the effects and underlying mechanisms of PEMF on disuse osteopenia and/or osteoporosis remain poorly understood. Herein, the efficiency of PEMF on osteoporotic bone microarchitecture, bone strength, and bone metabolism, together with its associated signaling pathway mechanism, was systematically investigated in hindlimb‐unloaded (HU) rats. Thirty young mature (3‐month‐old), male Sprague‐Dawley rats were equally assigned to control, HU, and HU + PEMF groups. The HU + PEMF group was subjected to daily 2‐hour PEMF exposure at 15 Hz, 2.4 mT. After 4 weeks, micro–computed tomography (µCT) results showed that PEMF ameliorated the deterioration of trabecular and cortical bone microarchitecture. Three‐point bending test showed that PEMF mitigated HU‐induced reduction in femoral mechanical properties, including maximum load, stiffness, and elastic modulus. Moreover, PEMF increased serum bone formation markers, including osteocalcin (OC) and N‐terminal propeptide of type 1 procollagen (P1NP); nevertheless, PEMF exerted minor inhibitory effects on bone resorption markers, including C‐terminal crosslinked telopeptides of type I collagen (CTX‐I) and tartrate‐resistant acid phosphatase 5b (TRAcP5b). Bone histomorphometric analysis demonstrated that PEMF increased mineral apposition rate, bone formation rate, and osteoblast numbers in cancellous bone, but PEMF caused no obvious changes on osteoclast numbers. Real‐time PCR showed that PEMF promoted tibial gene expressions of Wnt1, LRP5, β‐catenin, OPG, and OC, but did not alter RANKL, RANK, or Sost mRNA levels. Moreover, the inhibitory effects of PEMF on disuse‐induced osteopenia were further confirmed in 8‐month‐old mature adult HU rats. Together, these results demonstrate that PEMF alleviated disuse‐induced bone loss by promoting skeletal anabolic activities, and imply that PEMF might become a potential biophysical treatment modality for disuse osteoporosis. © 2014 American Society for Bone and Mineral Research.